Perlindungan Hukum Pemberi Fidusia Yang Beritikad Baik Dalam Peralihan Kredit Pembiayaan Kendaraan Bermotor Di Bawah Tangan - Wawan Andriawan (Fakultas Hukum Universitas Mataram, 2017)
This study aims to examine and analyze the legal protect of Good faith Fiduciary Giver in Transition of Motorized Vehicle Financing Under the Hands This research is a normative legal research by using the approach of legislation, method of concept approach and method of case approach. The theory used in this research is legal protection theory and legal certainty theory The results of this study found that the protection of the law for good-faith parties can take the form of repressive and preventive legal protection as stipulated in the Fiduciary Guaranty Act as well as second-party criminal responsibility in good faith transition under Article 23 paragraph (2) Jo Article 36 UUJF because in performing legal actions not in accordance with the provisions of the Fiduciary Guaranty Act and Article 372 of the Criminal Code.